If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -14 = 4 Reorder the terms: -14 + 6n = 4 Solving -14 + 6n = 4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 6n = 4 + 14 Combine like terms: -14 + 14 = 0 0 + 6n = 4 + 14 6n = 4 + 14 Combine like terms: 4 + 14 = 18 6n = 18 Divide each side by '6'. n = 3 Simplifying n = 3
| 4x-6=11x+16 | | 3x(x)=70 | | y+26=2y+8 | | 16-7x=-5x-4x | | 4(y+1)=2y+3+2y | | ln(x)=-1.082238098 | | y+26=2y+8-4 | | 125=-16t^2+125t+4 | | t+96=117 | | -7n+2=10 | | Y+8=2(x+4) | | 10x-2=181 | | 3(n+5)=4n+10-n+5 | | 8y^2+30+13= | | 13x-6x+15=6x+11 | | 123=-16t^2+123t+5 | | .12x-1=2+.75x | | n^2=3-2n | | 156=92-y | | Y=x^4+3x^2 | | m^2+10m=-21 | | 2x-(12)=4 | | -3h+14=8-h | | x^2=-6+7x | | .36(6)+.05x=.10(18+x) | | 8m-12=4+7m | | 4y-6=36 | | 7s-6=10+8s | | 5x-5=6+4x | | p^2-10=3p | | 4x-8x-12=-25 | | 5x+5=6+4x |